Surface immunoglobulins of erythrocytes and platelets in dogs naturally infected by Rangelia vitalii - Franca R.T. (2018)
© 2018Rangelia vitalii is a protozoan of the Babesiidae family that parasitizes domestic and wild dogs in South American countries. The main laboratory findings in blood samples from animals infected by R. vitalii are anemia and thrombocytopenia. The aim of this study was to detect IgM and IgG immunoglobulins on the surface of red blood cells and platelets, as well as to determine the percentage of reticulated platelets and reticulocytes in dogs naturally infected by R. vitalii. Blood samples from twenty dogs seen at the Veterinary Hospital of the Federal University of Santa Maria (UFSM) were divided into two groups: the diseased group consisted of blood samples from 10 animals with the diagnosis of rangeliosis, and the healthy group (control) consisted of samples from 10 healthy animals. All diseased dogs showed normocytic normochromic anemia but showed no differences (p > 0.05) in reticulocyte counts compared to healthy dogs. Moreover, IgM and IgG immunoglobulins were detected on the surface of the plasma membrane of red blood cells from both groups, but the amounts did not differ between groups (p > 0.05). Thrombocytopenia in infected animals was classified as severe. The percentage of reticulated platelets was higher (p < 0.001) in diseased dogs than in healthy animals. Diseased animals showed more IgM immunoglobulins bound to the surface of platelets than did the healthy group (p < 0.001). However, the amount of IgG bound to the surface of platelets was not different between groups. In conclusion, we showed that R. vitalii caused immune-mediated thrombocytopenia since IgM immunoglobulins were found on the surface of platelets of diseased dogs. We suggest that the binding of immunoglobulins on platelet surfaces contributes to early destruction of these cells and, consequently, alterations in hemostasis. An increase in reticulated platelets was noted in response to thrombocytopenia, indicating active thrombopoiesis.